(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
A study has been analyzed the “Pyridinium Chlorochromate Oxidation Species.” The method was analysed on reaction initial reaction of pyridinium chlorochromate. Further, This reaction has a mostly [cysteine] dependent effect. So, the plot study has been taken from 1/k` VS 1/[cysteine] It is a straight line with a positive slope and intersected at the valence axis, providing kinetic evidence for the complexation of cysteine ​​with reactive species. And the Chromium (III), It was determined that one of the products had no effect on the vaccine. As [H+] increases, the reaction increases and the [H+] degree is found to be less than One. The results were shows that Stoichiometry of the (Reaction) on product analysis and carried out chromatography and the stoichiometry of the reaction were pyridinium cysteine.